The effect of six weeks supplementation of green tea extracts on body composition and physical performance in judo athletes - Jeszka J.; Bajerska-Jarzebowska, J. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
Introduction A lot of published data [1,2] describe relationship between the percentage of lean body mass and physical performance of athletes. In some sports, competitions are taken in weight division (e.g. judo, boxing and wrestling), so athletes have to maintain limited body weight and high physical performance simultaneously. Long studies of sportsmen of these disciplines (showed that body weight gain (mainly do to increase of body fat occurred frequently in off-season periods. Overweight athletes (above their weight division) quite often apply rapid weight loss technique such as dehydratation, severely restricting food intake and occasionally, vomiting, diuretics and laxatives. These practices led to decrease physical performance, fatigue, depression, and feeling of isolation and even to anorexia nervosa or bulimia. In this study the possible benefits of dietary supplements - green tea extracts in reduction of body fat and maintenance of physical performance were investigated. Methods Twenty male judo athletes (20.0 ± 3.0 years old) were randomly assigned in a double-blind crossover study to either a green tea extract treatment (GT, n = 10) group or a placebo control (PC, n= 10) group. The criteria for selection of the subjects were following: members of the judo team for at least 2 seasons, injury free, not taking other substances that might aid athletic performance and weight loss for 4 weeks before the study began and no other supplements for 10 weeks, and maintenance of a balance diet. Subjects were involved in a preseason conditioning program. The GT group ingested 700mg of green tea extracts capsule (Olimp Green Tea, Sportatut, Poland) three times a day for 6 weeks. One capsule of green tea contained: 18mg of caffeine, 450mg of polyphenols and 330mg of catechin. The PC group followed the same supplementation schedule but was given a lactose placebo. Athletes were asked to avoid food and beverages containing caffeine for 6 weeks of supplementation period. The nutritional status was evaluated in the three separate occasions during the pretest period and during weeks 3 and 6 of the supplementation period, basing on anthropometrical indices: (height, weight) and body composition analysis using BIA technique (101S, AKERN - RJL). The measurements were conducted in morning hours. Energy expenditure was assessed by the non-invasive method of 24h monitoring of heart rate (Polar Electro Oy, Finland). The evaluation of the nutritive value of the athlete`s diet was conducted by 24-hour dietary recall. Each subject in the pretest period and during weeks 3 and 6 performed maximal incremental exercise tests on a cycle ergometer (Kettler, Germany) with a 15W/min increment until volitional fatigue. During the test VO2 (ml/min/kg), VE (l/min) and VT (l), (K4b2, Cosmed, Italy) were measured. In next day the judo athletes performed endurance cycle ergometer test to exhaustion at 70% VO2max, to determine the effect of green tea extract ingestion on endurance performance (time to exhaustion), respiratory exchange ratio - RER and substrate utilization (%FAT, %CHO, % PRO). Results Pre-supplementation data: The mean (+/- SD) age, height, body weight, percentage fat and free fat mass, VO2max in GT and PG groups were: 21.0 +/- 3.0yr, 20.0 +/- 3.0yr; 182.0 +/- 8.0cm, 176.0 +/- 7.5cm; 82.5 +/- 13.0kg, 71.0 +/- 11.5kg; 16.9 +/- 5.5%, 14.0 +/- 3.4%; 83.1 +/- 5.5%, 86.0 +/- 3.4% and 45.5 +/- 7.3ml/kg/min, 48.7 +/- 7.2 ml/kg/min respectively. Both groups was did not differ significantly at the start of the study in the respect of all these indexes. Body composition measures: After six weeks treatment period in the GT group significantly (p<0.05) decreased body fat mass (-1.34 +/- 1.8kg) while in the PG group fat mass slightly increase (0.9 +/- 1.5kg). Energy balance: In both groups energy intake in diets balanced their daily energy expenditures (GT: -74.0 +/- 80.0kcal/d, PG: 85.0 +/- 106.0kcal/d). RER and substrate utilization: RER parameter which was measured during the cycle ergometer test to exhaustion decreased significantly (p<0.05) in the GT group (from 1.10 +/- 0.1 to 0.92 +/- 0.1), whereas in the PG group was unchanged (PG: from 1.1 +/- 0.1 to 1.0 +/- 0.2). Additionally, reduced of RER parameter in GT was connected with significantly elevated of fat oxidation (p<0.01) from 5% before treatment period to 30% after sixth weeks of supplementation. Physical performance parameters: No significant differences in VO2max, VE, VT were observed before and post period of treatment in both groups, but time to exhaustion in GT group was shorter (p<0.05), while in PG group no differences were observed. Loss of body fat mass in GT group significantly correlated with RER parameter (r = -0.84, p<0.05) as well as with percentage of fat oxidation (r = 0.86, p<0.01). Discussion/Conclusion These results suggested that green tea extracts can be recommended as natural dietary supplements useful for maintaining low content of body fat in athletes.